The Ventrolateral Periaqueductal Gray Contributes to Depressive-Like Behaviors in Recovery of Inflammatory Bowel Disease Rat Model - Ko, Chih-Yuan; Yang, Ya-Bi; Chou, Dylan; Xu, Jian-Hua (Frontiers in Neuroscience, 2020)
Background Patients with inflammatory bowel disease (IBD) experience depression, even in the remission phase of IBD symptoms. Although mapping depression-associated brain regions through the gut-brain axis can contribute to understanding the process, the mechanisms remain unclear. Our previous results support the idea that glutamatergic transmission in the ventrolateral periaqueductal gray (vlPAG) mediates stress-induced depression-like behaviors. Thus, we hypothesize that the vlPAG plays a role in regulating depression during remission of IBD. Methods We used dextran sulfate sodium (DSS)-induced visceral pain model to evoke depression-like behaviors, assessed by tail suspension test (TST) and sucrose preference test (SPT), and electrophysiological recordings from vlPAG. Results Symptoms of animals modeling IBD were relieved by replacing DSS solution with normal drinking water, but their depression-like behaviors sustained. Moreover, the impairment of glutamatergic neurotransmission in vlPAG was sustained as well. Pharmacologically, microinfusion of the glutamate receptor 1 (GluR1) antagonist NASPM into vlPAG mimicked the depression-like behaviors. Furthermore, intra-vlPAG application of AMPA and AMPA receptor-mediated antidepressant (2R,6R)-hydroxynorketamine [(2R,6R)-HNK] reversed the DSS-induced depression-like behaviors in the remission phase of visceral abnormalities. Conclusion Our results suggest that vlPAG glutamatergic transmission mediates depression-like behaviors during remission of DSS-induced visceral pain, suggesting that vlPAG mapping to the gut-brain axis contributes to depression during remission of IBD.